Physiologic and biochemical measurements and response to noxious stimulation at various concentrations of MS‐222 in Koi (Cyprinus carpio). (22nd June 2012) - Stockman, Jonathan; Weber, Ernest Scott P; Kass, Philip H; Pascoe, Peter J; Paul‐Murphy, Joanne
Abstract Objective To evaluate the physiological effect and response to noxious stimulation at five concentrations of MS‐222 in koi (Cyprinus carpio). Study design Prospective experimental study. Animals Twenty‐one healthy adult unknown sex koi fish weighing mean 450 ± SD 120 g. Methods Each fish was exposed to five different concentrations of MS‐222 (50, 70, 110, 150 and 190 mg L−1) in a random sequence during the same anaesthetic event. For each concentration of MS‐222, vital functions such as heart rate (HR) (via Doppler) and opercular rate (OpR) were recorded after a standardized induction period. Response to two noxious stimuli in the form of haemostat clamp pressure applied on the tail and the lip was evaluated, and blood was drawn to measure biochemical and blood gas values. Results Decrease in response to noxious stimulation with an increase of MS‐222 concentration both for the lip (p = 0.0027) and the tail (p < 0.0001) stimulus was observed. Biochemical values were unaffected by the concentration of MS‐222 with the exception of lactate concentration which was weakly correlated with the duration of anaesthesia (r = 0.31, p < 0.001) and the number of times the fish was clamped or bled prior to sampling (r = 0.23, p < 0.001). Opercular rate decreased with the increase in anaesthetic concentration, and HR was not affected. Conclusions and clinical relevance Our results indicated a decrease in response to stimulus and a decrease in OpR that were associated with increased concentrations of MS‐222. This may assist in establishing anaesthetic protocols using MS‐222 in fish and supports the use of supramaximal pressure stimuli to teleost fish under variable MS‐222 concentrations as a model for future studies.